Improved Prediction of Salvage Antiretroviral Therapy Outcomes Using Ultrasensitive HIV-1 Drug Resistance Testing - Pou, Christian; Noguera-Julian, Marc; Pérez-Álvarez, Susana; García, Federico; Delgado, Rafael; Dalmau, David; Álvarez-Tejado, Miguel; Gonzalez, Dimitri; Sayada, Chalom; Chueca, Natalia; Pulido, Federico; Ibáñez, Laura; et al. (Clinical infectious diseases, 2014)
Background. The clinical relevance of ultrasensitive human immunodeficiency virus type 1 (HIV-1) genotypic resistance testing in antiretroviral treatment (ART)-experienced individuals remains unknown. Methods. This was a retrospective, multicentre, cohort study in ART-experienced, HIV-1-infected adults who initiated salvage ART including, at least 1 ritonavir-boosted protease inhibitor, raltegravir or etravirine. Presalvage ART Sanger and 454 sequencing of plasma HIV-1 were used to generate separate genotypic sensitivity scores (GSS) using the HIV db, ANRS, and REGA algorithms. Virological failure (VF) was defined as 2 consecutive HIV-1 RNA levels ≥200 copies/mL at least 12 weeks after salvage ART initiation, whereas subjects remained on the same ART. The ability of Sanger and 454-GSS to predict VF was assessed by receiver operating characteristic (ROC) curves and survival analyses. Results. The study included 132 evaluable subjects; 28 (21%) developed VF. Using HIVdb, 454 predicted VF better than Sanger sequencing in the ROC curve analysis (area under the curve: 0.69 vs 0.60, Delong test P = .029). Time to VF was shorter for subjects with 454-GSS < 3 vs 454-GSS ≥ 3 (Log-rank P = .003) but not significantly different between Sanger-GSS < 3 and ≥3. Factors independently associated with increased risk of VF in multivariate Cox regression were a 454-GSS < 3 (HR = 4.6, 95 CI, [1.5, 14.0], P = .007), and the number of previous antiretrovirals received (HR = 1.2 per additional drug, 95 CI, [1.1, 1.3], P= .001). Equivalent findings were obtained with the ANRS and REGA algorithms. Conclusions. Ultrasensitive HIV-1 genotyping improves GSS-based predictions of virological outcomes of salvage ART relative to Sanger sequencing. This may improve the clinical management of ART-experienced subjects living with HIV-1. Clinical Trials Registration. NCT01346878.